PENGATURAN HUKUM TERHADAP PRIVATISASI SEMPADAN PANTAI OLEH PENGUSAHA PARIWISATA DI PROVINSI BALI - Kusuma Sanjiwani, Putri (Jurnal Analisis Pariwisata; Vol 16 No 1 (2016): Jurnal Analisis Pariwisata (Juli 2016), 2017)
The research titled “Legal Arrangements of the Privatization of Coastal Line by Entrepreneur Tourism in Bali Province”. This research is motivated by the practice of privatization of tourism entrepreneurs on the coastal line in the coastal area of the Bali island. Coastal line is a public space and regulated in the legislation, coastal line should not be owned privately. Local communities are the most disadvantaged on the privatization practices. Local communities lose public space, lose the right and freedom to enjoy public facilities, loss of access and place for carry out religious rituals, and children lost their playground. The issue that arises is how the legal arrangements regarding the privatization of coastal line by tourism entrepreneurs in the province of Bali? How the Bali Provincial Government policies in addressing the privatization of coastal line in the province of Bali? Method used in the writing of the journal of the rule of law against the privatization of the coastal line in the province of Bali tourism entrepreneurs are using normative legal research methods. Method used in the writing of the journal of the rule of law against the privatization of the coastal line in the province of Bali tourism entrepreneurs are using normative legal research methods. Writing this journal approach and conceptual legislation to be able to analyze the problems with the theory of law to analyze a problem with the applicable rules in accordance with the legislation in the hierarchy of the sort order for the legislation in force in Indonesia. Explores the concept of policy in assessing the direction of government policy in issuing policies towards the privatization of coastal line by tourism entrepreneurs. The results showed the regulation of coastal line is already regulated in legislation but there is vagueness that occurs in the utilization norms coastal line for the sake of tourism. The local government has the authority to crack down on the practice of privatization by tourism entrepreneurs. Need formation of the governing body of the local government consisting of local communities to restore the function and bene ts of coastal line as a public space. Practice privatization should be subject to sanctions explicitly either civil penalties or criminal sanctions. Legal framework established to overcome this problem is in the form of regulations governing the use of coastal line to the area of tourism and rules of the governing body coastal border.